2020
DOI: 10.1007/s10461-020-03041-7
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Depression and HIV Care Engagement Outcomes Among Patients Newly Initiating ART in Lilongwe, Malawi

Abstract: As in other sub-Saharan countries, the burden of depression is high among people living with HIV in Malawi. However, the association between depression at ART initiation and two critical outcomes—retention in HIV care and viral suppression—is not well understood. Prior to the launch of an integrated depression treatment program, adult patients were screened for depression at ART initiation at two clinics in Lilongwe, Malawi. We compared retention in HIV care and viral suppression at 6 months between patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Our finding that an HIV positive test result was significantly associated with increased odds of reporting depression symptoms contributes to the evidence asserting that depression is common and higher among people living with HIV compared to the general population (Bernard et al, 2017, August;Bigna et al, 2019;Lofgren et al, 2020;Stockton et al, 2020). In our study, a third (29.4%) of people reporting HIV positive test results reported depression symptoms compared to nearly one in five (18.1%) with an HIV negative test result.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Our finding that an HIV positive test result was significantly associated with increased odds of reporting depression symptoms contributes to the evidence asserting that depression is common and higher among people living with HIV compared to the general population (Bernard et al, 2017, August;Bigna et al, 2019;Lofgren et al, 2020;Stockton et al, 2020). In our study, a third (29.4%) of people reporting HIV positive test results reported depression symptoms compared to nearly one in five (18.1%) with an HIV negative test result.…”
Section: Discussionsupporting
confidence: 67%
“…Mental health difficulties, including major depressive disorders (MDD) and disability, constrain the quality of life for people living with HIV and reduce their ability to benefit from HIV services and are often used as a proxy for quality of life. A study in Malawi found a prevalence of depression of 27% among adults initiating ART (Stockton et al, 2020). In Botswana, Gupta and colleagues found in a population-based study that 30% of men and 25% of women living with HIV screened positive for depression (Gupta et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the presence of depression in a higher percentage of patients, and the presence of constitutional symptoms in these patients may be one of the reasons for over-reporting of depression in these patients. [ 11 16 17 25 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…Bivariate and multivariate generalized linear modelling (GLM) were used to calculate the crude and adjusted MDs and the corresponding 95% confidence intervals (CIs) comparing the level of depressive symptoms across levels of HIV disclosure. Because persons newly diagnosed with HIV have been shown to have elevated risks of depression [35] and because they may not have enough time to disclose their HIV status, all analyses were a priori stratified by whether HIV was diagnosed prior to or during the current pregnancy.…”
Section: Statistical Analysesmentioning
confidence: 99%